VARIATIONS IN THE CLINICAL AND ANAESTHETIC PARAMETERS DURING ADMINISTRATION OF ROPIVACAINE AND FENTANYL AS LUMBOSACRAL ANAESTHESIA IN GOATS - L. Kumari; A. K. Sharma; L. Kumari; Chandrakala; M. P. Sinha; M. K. Gupta (Journal of Animal and Plant Sciences, 2017)
The aim of study was to assess the quality of analgesia and record the alteration in clinico-anesthetic indices following epidural administration of ropivacaine alone and its combination with fentanyl. A total of 10 clinically healthy goats of 1-3 years aged and weighing between 10-15 kg were used for the present experiment. All the animals were randomly divided into two groups of five animals each. Ropivacaine (0.75%) @ 1 mg/kg BW was administered epidurally at the lumbosacral space in group 1 whereas, the animals of group 2 were given fentanyl @ 2 µg/kg BW in combination with ropivacaine hydrochloride (1 mg/kg BW). Rectal temperature, respiration rate and heart rate showed non- significant (P>0.05) variations in both the groups. Duration of analgesia in the different parts of hindquarter was longer in group II as compared to group I. Analgesia, motor incoordination and sedation depicted greater degree in group II.  The results suggest that the ropivacaine alone or in combination with fentanyl produced effective analgesia (sensory and motor) of different parts of the hindquarters with little effect on physiology. However, the combination groups manifested higher degree of analgesia, motor incoordination and sedation.
Keywords: Analgesia; clinico- anaesthetic variations; fentanyl; goats; ropivacaine